REKONSTRUKSI ISLAM JAWA SARIDIN DALAM FILM SARIDIN; STUDI SERIAL FILM SARIDIN PRODUKSI CMC (CREATIVE MEDIA COMMUNITY) PATI, JAWA TENGAH - Salamah, Lanal Mauludah Zuhrotus (Khazanah: Jurnal Studi Islam dan Humaniora, 2017)
This article describes a typical Javanese Islamic image that is featured in the movie series "Saridin" featuring Saridin as the main play. In his time, Saridin was one of the most important figures in the propagation of Islamic preaching in Pati, his birthplace, with a distinctive religiosity which in some ways was still influenced by Hindu-Buddhist traditions, such as; semedi, selametan, nyadran, and tirakatan. It is an example of a form of Islam-acculturation, which in the macro context is familiarly called "Islam Nusantara". Islam Nusantara is often accused of being a destroyer of the basics of true Islam, which for the pro-Islamic group of acculturation means otherwise. Initially, the film was released by the director, Alman Eko Darmo, along with his friends of the Pati humanist as an expression of their anxiety about the static ketoprak art in Pati, as well as the rebirth of Saridin's classic spectacles which are regularly featured in Ketoprak and last in the Mp3 version. On June 30, 2016, CMC successfully conducted the inaugural launch of the Saridin movie series; Saridin Andum Waris, Saridin Ngerombang, and followed by Saridin Geger Palembang and Saridin Ondo Rante in September 2016. The films have received various responses from various parties, including the observers of da'wah of Islamic –acculturation. For them the presence of Saridin the movie series contains educational message that is appropriate for their da'wah media.